Toward A Collaborative Smart City: A Play-Based Urban Living Laboratory in Boston. Issue 2 (20th January 2023) - Gordon, Eric; Harlow, John; Teng, Melissa; Christoferetti, Elizabeth
ABSTRACT: This article reports on an urban living laboratory that designed a suite of play-based prototypes, as an attempt to "institution" collaborative smart city governance in the city of Boston. This project was called "Beta Blocks, " and it geographically defined "Exploration Zones, " governed by local residents and business owners, who decided whether, where, and why to temporarily install technologies in the public realm. To recruit and facilitate the participation of Zone Advisory Group members, the authors fabricated a lavender, parking-space-sized, inflatable art exhibition (Beta Blob) that hosted a suite of public-facing activities. Although the composite model failed at "institutioning" itself into Boston's government through this prototype, the discrete components succeeded in centering play in public learning situations and prototyping a model for collaborative governance between publics, and the public and private sectors.